Arsenic in surface soils affected by mining and metallurgical processing in K. Mitrovica region, Kosovo - Stafilov, Trajce; Aliu, Milihate; Sajn, Robert (MDPI AG, 2010)
The results of a study on the spatial distribution of arsenic in topsoil (0-5 cm) over the K. Mitrovica region, Kosovo, are reported. The investigated region (300 km(2)) was covered by a sampling grid of 1.4 km × 1.4 km. In total, 159 soil samples were collected from 149 locations. Inductively coupled plasma-mass spectrometry (ICP-MS) was applied for the determination of arsenic levels. It was found that the average content of arsenic in the topsoil for the entire study area was 30 mg/kg (from 2.1 to 3,900 mg/kg) which exceeds the estimated European arsenic average in topsoil by a factor of 4.3. Contents of arsenic in the topsoil exceeded the optimum value recommended by the new Dutchlist (29 mg/kg As) in 124 km(2). The action value (55 mg/kg As) was exceeded in 64 km(2), with the average content of 105 mg/kg (from 55 to 3,900 mg/kg As).